Rabies surveillance in Senegal 2001 to 2015 uncovers first infection of a honey‐badger. Issue 5 (23rd February 2022) - Faye, Martin; Faye, Oumar; Paola, Nicholas Di; Ndione, Marie Henriette Dior; Diagne, Moussa Moise; Diagne, Cheikh Tidiane; Bob, Ndeye Sakha; Fall, Gamou; Heraud, Jean‐Michel; Sall, Amadou Alpha; Faye, Ousmane
Abstract: Despite the establishment of Rabies surveillance in animals and humans since 2008, there is a lack of data on its circulation, dynamic of transmission and real burden in Senegal. To better understand the molecular epidemiology of rabies virus in Senegal, we investigated the genetic diversity of 18 new characterized Senegalese rabies virus sequences collected over 14 years, including a honey‐badger‐related isolate. Phylogeographic analyses demonstrated that the Senegalese isolates belong to a monophyletic cluster into the Africa‐2 clade and supported two RABV introductions in Senegal from West‐African neighbour countries, 36–40 years ago. Our study is noteworthy for reporting on the first characterization of an African honey‐badger‐related rabies virus that did not have the N‐glycosylation site NKT at position 338‐G of the glycoprotein. The identified amino acid polymorphisms found in the Senegalese rabies virus sequences are worthy of further investigation. Although a strong multidisciplinary stepwise cooperation is important for the successful elimination of Rabies in dog populations in Senegal by 2030, the establishment of surveillance in wildlife could be necessary to avoid future re‐introductions into domestic hosts.